Perancangan Pasar Datuk Rubiah Bagansiapiapi Dengan Pendekatan Arsitektur Melayu Dan Cina - Yogistira, Yogistira; Faisal, Gun; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Datuk Rubiah Market, located in Jl. Sumatra is a place that plays an important role in collecting the needs of the people of Bagansiapiapi. Problems that occur in Datuk Rubiah are many shortages of facilities such as trash bins, management offices, unloading areas, kiosks and booths that are lacking for sellers. The market arrangement also looks poor, that is, the circulation in and out of the market is not appropriate so that buyers are piling up, lack of parking lots and drainage facilities is also a problem caused in this market. therefore the need for a new Design Datuk Rubiah Market both in terms of buildings and land area. The design method used in the design of the Datuk Rubiah Market is with the principles of Chinese and Malay Architecture. The concept used in the design of the Rubiah Datuk market is negotiation.Keywords: Bagansiapiapi, Datuk Rubiah Market, Chinese and Malay Architecture